An Analysis of the Features of the Organisation of Tourist Activities in the Conditions of the War in Ukraine - Halyna Zavarika; Olena Zelenko (Studia Regionalne i Lokalne)
The article reveals topical issues regarding the consequences, possibilities of operation, and the restoration of tourism in the post-war territories of Ukraine in the conditions of military aggression of the Russian Federation. The purpose of the study was to analyse the organisation of tourist activities under the conditions of martial law in Ukraine. The article highlights preliminary data on the losses of the tourism industry in Ukraine as well as analyses and systematises specific examples of damaged natural and cultural-historical heritage on the territory of Ukraine. The peculiarities of the functioning of the subjects of the tourism industry in the conditions of the war in Ukraine are evaluated and the essence of the post-war territories is indicated. Directions for saving tourist activity in the post-war territories of Ukraine as a result of the military actions of the aggressor country are proposed. The proposals indicated in this work will be useful to all Ukrainian communities whose tourism industry has suffered great losses as a result of the military aggression. It will also be useful for representatives of the tourism industry of other countries who want to prevent, if possible, the destructive effects of war.